1985
DOI: 10.1042/bj2260403
|View full text |Cite
|
Sign up to set email alerts
|

Heat exposure and hypothyroid conditions decrease hydrogen peroxide generation in liver mitochondria

Abstract: Exposure of rats to heat (39 +/- 1 degree C) decreased H2O2 generation in mitochondria of the liver, but not of the kidney or the heart. The effect was obtained with three substrates, succinate, glycerol 1-phosphate and choline, with a decrease to 50% in the first 2-3 days of exposure, and a further decrease on longer exposure. The dehydrogenase activity with only glycerol 1-phosphate decreased, which is indicative of the hypothyroid condition, whereas choline dehydrogenase activity remained unchanged and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 29 publications
1
43
0
Order By: Relevance
“…GSH: GSSG in tissue is now considered one of the important markers of oxidative stress. The decrease in its ratio and the restoration to its normal value by T3 administration confirms the critical role of thyroid hormone in regulating mitochondrial oxidative stress [13].…”
Section: Antioxidant Statusmentioning
confidence: 73%
See 1 more Smart Citation
“…GSH: GSSG in tissue is now considered one of the important markers of oxidative stress. The decrease in its ratio and the restoration to its normal value by T3 administration confirms the critical role of thyroid hormone in regulating mitochondrial oxidative stress [13].…”
Section: Antioxidant Statusmentioning
confidence: 73%
“…In hypothyroidism, a decrease in free radical production is expected because of the metabolic supression brought about by the decrease in thyroid hormone levels [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in rat models have also demonstrated an increase in free radical production and lipid peroxide levels during hypermetabolic state (4,7,8), while the hypometabolic state induced by hypothyroidism is associated with a decrease in free radical production (9) and lipid peroxidation products (10). However, alterations in ROS levels have not been demonstrated in the cells or tissues of patients having thyroid dysfunction.…”
mentioning
confidence: 97%
“…On the other hand, hypothyroidism is associated with cellular ionic imbalance, augmented oxidative stress, and decreased GSH and glutathione-Stransferase (GST) [2,5,6,[39][40][41]. Also, a reduction in the levels of free radical is predictable on account of the metabolic inhibition by the hypothyroid state [42][43][44]. This disturbance has deleterious effect on the health of the newborns and adulthood [5-10].…”
Section: Commentarymentioning
confidence: 99%